Analysis of the Effect of Foreign Debt on Indonesia's Economic Growth (2017-2021) - Aisyah Ameilia; Cut Aliyyah; Fadila Nisa; Andri Hasmawi; Batubara, Ade Andriani (Outline Journal of Economic Studies, 2023)
This study aims to analyze the effect of foreign debt on Indonesia's economic growth in 2017-2021. The data used are time series data and secondary data was obtained through the official websites of BPS and BI. GDP data at constant prices reflecting Indonesia's economic growth obtained through BPS is used as the dependent variable. Meanwhile, foreign debt data obtained through BI is used as an independent variable. The research method used is a simple linear regression method with Ordinary Least Square (OLS) and the classical assumption test to ensure that the research model obtained is not biased. The results of the study showed that foreign debt has a positive and significant influence on Indonesia's economic growth with a Prob. value of 0.0290 < 0.05. The R-squared value of 0.838482 indicated that 83.8482% of Indonesia's economic growth can be explained through variations in the value of foreign debt. While the remaining 17.1518% are other variables not included in this study.